2020
DOI: 10.1002/tal.1703
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic interference effects of a proposed taller high‐rise building on wind pressures on existing tall buildings

Abstract: When a large super high-rise building taller than the surrounding tall buildings is built in a dense urban area, the aerodynamic interference effects of the surrounding buildings on the proposed building attract much attention, while the interference effects of the taller high-rise building on the nearby existing buildings are often ignored.Based on a series of wind tunnel tests, the interference effects of a proposed taller high-rise building, an adjacent equal-height partner building, and relatively short ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Nagar et al (2020) [19] studied pressure coefficient and IF for different interference conditions of square and H plan shaped tall buildings having same plan area and reported that H plan shape is subjected to higher pressure than the square model. Proximity effects on an existing target tall building due to proposed super tall building with a pair of similar buildings adjacent to the target building has been studied by Quan et al (2020) [20]. It was reported that the aerodynamic response of the target building increased considerably when the proposed super building exists in the flow direction upstream the target building.…”
Section: Introductionmentioning
confidence: 99%
“…Nagar et al (2020) [19] studied pressure coefficient and IF for different interference conditions of square and H plan shaped tall buildings having same plan area and reported that H plan shape is subjected to higher pressure than the square model. Proximity effects on an existing target tall building due to proposed super tall building with a pair of similar buildings adjacent to the target building has been studied by Quan et al (2020) [20]. It was reported that the aerodynamic response of the target building increased considerably when the proposed super building exists in the flow direction upstream the target building.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [39] and Quan et al [40] studied the proximity effects on an existing target tall building with existence of a proposed super tall building and a pair of adjacent buildings of similar height. The results showed that the aerodynamic response of the target building was considerably increased when the proposed super-tall building existed upstream.…”
Section: Introductionmentioning
confidence: 99%